Key Developments in the Potential of Curcumin for the Treatment of Peripheral Neuropathies - Martial Caillaud; Yu Par Aung Myo; Bryan D. McKiver; Urszula Osinska Warncke; Danielle Thompson; Jared Mann; Egidio Del Fabbro; Alexis Desmoulière; Fabrice Billet; M. Imad Damaj (MDPI AG, 2020)
Peripheral neuropathies (PN) can be triggered after metabolic diseases, traumatic peripheral nerve injury, genetic mutations, toxic substances, and/or inflammation. PN is a major clinical problem, affecting many patients and with few effective therapeutics. Recently, interest in natural dietary compounds, such as polyphenols, in human health has led to a great deal of research, especially in PN. Curcumin is a polyphenol extracted from the root of Curcuma longa. This molecule has long been used in Asian medicine for its anti-inflammatory, antibacterial, and antioxidant properties. However, like numerous polyphenols, curcumin has a very low bioavailability and a very fast metabolism. This review addresses multiple aspects of curcumin in PN, including bioavailability issues, new formulations, observations in animal behavioral tests, electrophysiological, histological, and molecular aspects, and clinical trials published to date. The, review covers in vitro and in vivo studies, with a special focus on the molecular mechanisms of curcumin (anti-inflammatory, antioxidant, anti-endoplasmic reticulum stress (anti-ER-stress), neuroprotection, and glial protection). This review provides for the first time an overview of curcumin in the treatment of PN. Finally, because PN are associated with numerous pathologies (e.g., cancers, diabetes, addiction, inflammatory disease...), this review is likely to interest a large audience.